2002
DOI: 10.1111/j.1749-6632.2002.tb04306.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of BRX‐220 against Peripheral Neuropathy and Insulin Resistance in Diabetic Rat Models

Abstract: Bimoclomol (BML), a symptomatic antidiabetic agent, has been developed by Biorex R & D Co. to treat diabetic neuropathy and retinopathy. BRX‐220, an orally active member of the BRX family, has been developed to treat diabetic complications and insulin resistance (IR) as a follow‐up compound. The effect of BRX‐220 on peripheral neuropathy was examined in rats with diabetes (type 1) induced by administration of a β‐cell toxin, streptozotocin (STZ, 45 mg/kg iv). Nerve functions were evaluated by electrophysiologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 14 publications
1
24
0
Order By: Relevance
“…Therefore, despite the non-linear pattern of changing in HSP expression, the data suggest a possible inverse relationship between the level of HSP and neuropathological change in DM. Consistent with this notion, compounds known to co-induce HSP were able to improve diabetic peripheral neuropathy (Kurthy et al, 2002) and wound healing (Vigh et al, 1997). Although the development of diabetic complications is associated with a progressive decline in the expression of HSPs, mice with a genetic knock-out of the inducible isoforms of HSP70 (HSP70.1 and 70.3) did not develop any more severe neurophysiological deficits than were observed in wild-type diabetic mice (Urban et al, 2010).…”
Section: Impaired Hsp Protection In Dpnsupporting
confidence: 56%
See 2 more Smart Citations
“…Therefore, despite the non-linear pattern of changing in HSP expression, the data suggest a possible inverse relationship between the level of HSP and neuropathological change in DM. Consistent with this notion, compounds known to co-induce HSP were able to improve diabetic peripheral neuropathy (Kurthy et al, 2002) and wound healing (Vigh et al, 1997). Although the development of diabetic complications is associated with a progressive decline in the expression of HSPs, mice with a genetic knock-out of the inducible isoforms of HSP70 (HSP70.1 and 70.3) did not develop any more severe neurophysiological deficits than were observed in wild-type diabetic mice (Urban et al, 2010).…”
Section: Impaired Hsp Protection In Dpnsupporting
confidence: 56%
“…Indeed, pharmacological induction of HSP70 with the hydroxylamine derivative BGP-15, -lipoic acid or GGA improved glucose tolerance in insulin-resistant mice (Chung et al, 2008), rats (Gupte et al, 2009a) and monkeys (Kavanagh et al, 2011), respectively. Notably, administration of a HSP co-inducer BRX-220 to STZ-diabetic rats dose-dependently reduced insulin resistance and was associated with improved peripheral sensory and motor nerve deficits (Kurthy et al, 2002). In Gupte's study of rats fed with high-fat diet, addition of an HSP70 inhibitor diminished the heat-induced JNK depression, indicating that inhibition of JNK activation by heat-shock is largely HSP70-dependent (Gupte et al, 2009b).…”
Section: Hsp Inhibits Inflammation and Stress Kinasesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, patients with type 2 diabetes experienced reductions in blood glucose concentration and symptomatic neuropathy after receiving regular hot-tub treatment (Hooper, 1999(Hooper, , 2003. In diabetic rats, the HSF1 activators bimoclomol and arimoclomol (BRX-220) improved diabetic wound healing and nerve conduction deficits, respectively (Vígh et al, 1997;Kü rthy et al, 2002); direct HSF1 activators may provide another pharmacologic route to modulating genes that express chaperones and antioxidant proteins (Neef et al, 2011). The potential effectiveness of ␣-lipoic acid in treating DPN has already been noted and ␣-lipoic acid therapy has been normalized.…”
Section: -Kda Heat-shock Protein and Neuroprotection In Dpnmentioning
confidence: 99%
“…More importantly, a 41°C heat treatment once a week for 12 weeks improved glucose tolerance and reduced stress-activated signaling in rats fed by a high-fat diet suggesting a crosstalk between the development of HSF1 dependent thermotolerance and metabolic stress tolerance [41]. The chaperone coinducer bimoclomol derivative, BRX-220 was also able to improve insulin sensitivity of both Zucker fatty diabetic rats, and streptozotocin-treated diabetic rats [42]. Finally, a recent study demonstrated that besides heat shock either overexpression or pharmacologic induction of Hsp70 by a novel chaperone co-inducer BGP-15 was sufficient to prevent the development of obesity-induced insulin resistance in fat-fed mice [43].…”
Section: Obesity and Diabetes As A Metabolic Distress: The Protectivementioning
confidence: 82%